A transport justice approach to integrating vulnerable road users with automated vehicles. (December 2022) - Martínez-Buelvas, Laura; Rakotonirainy, Andry; Grant-Smith, Deanna; Oviedo-Trespalacios, Oscar
Abstract: Connected and automated vehicles (CAVs) are expected to revolutionise transport worldwide and transform urban life. However, there are many unknowns concerning the impacts of these technologies in terms of sustainability, justice, and safety. It has been suggested that CAVs may exacerbate inequities and safety disparities concerning the interaction of vulnerable road users (VRUs) with motorised transport. This paper investigates the justice issues that CAVs policy needs to address concerning VRUs. Our approach to studying CAVs' capabilities and their potential perverse outcomes uses transport justice as an evaluative framework. The justice-related outcomes discussed include: traffic injuries, impact on sharing road responsibilities, loss of on-street space, access to technology, inclusion for disabled and older adults, CAV technological development, and impact of congestion and air pollution. The paper proposes a future research agenda emphasising areas where CAVs may positively impact VRUs.